Factoring economic costs into conservation planning may not improve agreement over priorities for protection. Issue 1 (December 2017) - Armsworth, Paul; Jackson, Heather; Cho, Seong-Hoon; Clark, Melissa; Fargione, Joseph; Iacona, Gwenllian; Kim, Taeyoung; Larson, Eric; Minney, Thomas; Sutton, Nathan
Abstract Conservation organizations must redouble efforts to protect habitat given continuing biodiversity declines. Prioritization of future areas for protection is hampered by disagreements over what the ecological targets of conservation should be. Here we test the claim that such disagreements will become less important as conservation moves away from prioritizing areas for protection based only on ecological considerations and accounts for varying costs of protection using return-on-investment (ROI) methods. We combine a simulation approach with a case study of forests in the eastern United States, paying particular attention to how covariation between ecological benefits and economic costs influences agreement levels. For many conservation goals, agreement over spatial priorities improves with ROI methods. However, we also show that a reliance on ROI-based prioritization can sometimes exacerbate disagreements over priorities. As such, accounting for costs in conservation planning does not enable society to sidestep careful consideration of the ecological goals of conservation. Prioritising areas for conservation is hindered by disagreements over ecological targets. Here, Armsworth et al. combine a simulation approach and case study to test if considering economic return on investment aids in prioritisation, and find that its impact on reaching agreements varies greatly.